The relationship between human resource development factors, career growth and turnover intention: the mediating role of organizational commitment - Nawaz, Muhammad Shahid; Pangil, Faizuniah (Growing Science Ltd., 2016)
Retaining the best employees is of high concern for most organizations and this issue has become a significant focus of attention for many researchers. For this reason, this paper discusses different factors which influence the employee turnover intention-behavior in the organization, specifically to examine the effect of salary, performance appraisal, training & development and career growth on turnover intention. In addition, based on the social exchange theory this paper explains the mediating role of organizational commitment in the relationship between human resource development factors, career growth and turnover intention. A cross sectional, survey data study is undertaken to investigate the relationships in a sample of 270 full time faculty members employed in different private universities of Pakistan. Partial Least Square two step path modeling is used to test the direct and the indirect hypothesis of the study. The results of PLS (SEM) path modeling reveal that human resource development factors specially salary and performance appraisal were negatively associated with turnover intention. In addition, the results also indicate that career growth had significant relationships with turnover intention. Moreover, out of four dimensions of career growth, only two dimensions, namely promotion speed and remuneration growth, have strong influence on turnover intention. Finally, in terms of organizational commitment as mediating variable between the relationships of salary, performance appraisal, career growth and turnover intention, four out of six variables indicate partial mediation including career growth (career goal progress), career growth (promotion speed), career growth (remuneration growth) and performance appraisal.